Green Solvents for Eco-friendly Synthesis of Bioactive Heterocyclic Compounds - Dolzhenko, Anton; Dolzhenko, A. (Elsevier, 2014)
Use of safer solvents satisfies green chemistry practices. From the green chemistry perspective, the best solvent for reactions is no solvent. However, this ideal situation is not always achievable and choice of more eco-friendly solvents becomes critical. This chapter is dedicated to the synthesis of heterocyclic compounds using supercritical carbon dioxide and unconventional eco-friendly solvents with good biodegradability potential, such as polyethylene glycols (PEGs) and some bio-derived solvents (glycerol, ethyl lactate, and gluconic acid aqueous solution). These reaction media have enormous potential for use in medicinal chemistry with many advantages over conventional organic solvents. Supercritical carbon dioxide differs from the conventional solvents by its extremely low gas-like viscosity and great diffusivity. At the same time, supercritical carbon dioxide possesses an excellent profile from the health, safety, and environment perspective. Moreover, being an excellent solvent, supercritical carbon dioxide also acts as a very useful green reagent in a number of important transformations, including heterocyclizations. PEGs are nontoxic and biodegradable polymers with molecular weight ranging from 200 to 20,000 g/mol. This provides a good choice of PEGs for a better reaction outcome. In a number of reactions, PEG, being a solvent, also plays a role of a catalyst promoting the reaction. Bio-derived solvents such as glycerol, ethyl lactate, and gluconic acid possess enormous potential for heterocyclic chemistry, especially in combination with other green chemistry tools like microwave irradiation. Use of these unconventional solvents in the synthesis of heterocyclic compounds of biological importance is exemplified in this chapter.